A novel Mn-based P2/tunnel/O3′ tri-phase composite cathode with enhanced sodium storage properties. Issue 19 (10th February 2020) - Wang, Dong; Liu, Yihua; Wu, Zhenguo; Liu, Xiaohong; Qu, Jie; Liu, Hao; Ming, Yong; Zhong, Yanjun; Zhong, Benhe; Guo, Xiaodong
Abstract : A novel P2/tunnel/O3′ tri-phase composite Na0.7 Bi0.01 MnO2 is developed for the first time by the Na + -site modification of Bi 3+ for a high-performance cathode in SIBs. Abstract : A novel P2/tunnel/O3′ composite Na0.7 Bi0.01 MnO2 cathode is developed via the Na + -site modification of Bi 3+ in layer structure Na0.7 MnO2 for the first time. Superior electrochemical performance with a high capacity retention of ∼86.5% after 300 cycles at 2C is obtained. Moreover, the tri-phase structure can also serve as a model material, which intuitively evidences the environmental structural stability order: tunnel > P2 > O3′.